Integrating Environmental Fiscal Tools and Clean Energy for Climate Mitigation: An International Perspective - Ghraieb, Ikram (International Journal of Energy Economics and Policy, 2025)
This study examines how effective environmental policies, specifically environmental taxation and renewable energy use, are in reducing climate change in developed countries from 1995 to 2023. Using a dynamic panel threshold model, we evaluate if the connection between these environmental tools and carbon emissions shows non-linear patterns, with environmental taxation acting as the threshold variable. Our findings reveal significant threshold effects, suggesting that the impact of renewable energy use on reducing emissions is stronger once a certain tax level is surpassed. Additionally, the results emphasize how environmental taxes and clean energy adoption work together to achieve substantial reductions in emissions. We conduct tests for cross-sectional dependence and panel unit roots to ensure the results are reliable, and we use system GMM to handle endogeneity issues. This study adds to the literature by exploring taxation and renewable energy within a dynamic threshold framework, which has not been widely studied before. The policy implications indicate that increasing green taxation and fostering clean energy investments can be essential strategies for reaching climate targets in developed countries.